10 - Decentralisation as Ethnic Closure, with Special Reference to a Declining Negotiated Access to Natural Resources in Western Ethiopia - Feyissa, Dereje (Africa Development, 2006)
Between the Anywaa and the Nuer, the two neighbouring people in the Gambela regional state in western Ethiopia, the Anywaa are better endowed with access to and control over vital natural resources. Occupying an economic fringe, the Nuer have used various strategies to access these resources. After their initial violent expansion into Anywaa territories, the Nuer have largely reoriented their strategy to peaceful means: social networking and the instrumentalisation of inter-ethnic exchanges. This was due to their capacity to create a shared cultural space centring on the notion of the first-comer to regulate entitlement issues. In this paper, I explore the process of local-level integration and how decentralisa- tion and the new political order have shifted the mode of inter-ethnic relations from compromise and negotiation to competition and confrontation. The paper argues that this is so partly because, despite the decentralisation rhetoric, the state maintains a hegemonic status by claiming ultimate ownership over the vital means of production—the land. Drawing on the experience of the Gambela regional state, the paper argues that decentralisation in Ethiopia has not brought its intended result—local empowerment. Instead, decentralisation is experienced in the form of elite political competition, while seriously undermining local forms of integration. Above all, decentralisation and the new political order have meant the growing relevance of extra-local bases of entitlement over natu- ral resources.